COMPREHENSIVE STUDY OF EXTRACTION AND APPLICABILITY OF NANOSILICATE PARTICLES FROM NATURAL WASTE FOR BIOPOLYMER REINFORCEMENT (Nigerian Journal of Technology, 2025)
Biopolymers have emerged as a promising alternative to traditional petroleum-based plastics owing to their inherent biodegradability and renewability. However, augmenting their mechanical and barrier properties remains pivotal for diverse applications, particularly in packaging applications. This study explores corncob nano-silica (ccnSi) extraction, evaluating its performance in biopolymer films. A synergistic chemical-mechanical process yielded uniformly sized ccnSi particles (69.23-97.70 nm). To optimize ccnSi incorporation, surface treatments with varying NaOH concentrations (3.0M, 3.5M, 4.0M) were applied. The extracted ccnSi's performance metrics rivaled commercial nano-silica (cnSi). X-ray fluorescence (XRF) analysis unveiled a heightened silicon content in ccnSi (94 %) relative to cnSi (71.61 %). Scanning electron microscopy (SEM) and Energy dispersive X-ray (EDX) analyses substantiated the commendable dispersion and amorphous characteristics of the ccnSi/biopolymer composites. Using Fourier transform infrared spectroscopy (FT-IR) provided empirical evidence for the existence of groups of silanol as well as the silane, signifying surface modifications. Substantial surface areas (324.9-833.6 m²/g) were ascertained through Brunauer-Emmett-Teller (BET) analysis, a finding further affirmed through the dynamic light scattering (DLS) and particle size distribution (PSD) measurements. The incorporation of ccnSi markedly elevated the tensile strength of biopolymer films (0.572 MPa) in contrast to cnSi (0.49 MPa). Thermogravimetric and Differential thermal analysis (TGA-DTA) indicated commendable thermal stability, with polymer degradation initiating at 400 °C. The glass transition temperature (Tg) of 32 °C, coupled with the amorphous nature confirmed by Differential scanning calorimetry (DSC), underscores the promising potential of ccnSi as a biopolymer. This research underscores the successful extraction and application of ccnSi in biopolymer-based films, presenting a paradigm shift towards enhanced performance and heightened environmental sustainability in next-generation packaging materials.